ANALISIS SOCIAL RETURN ON INVESTMENT (SROI) PADA PERUSAHAAN PEMENANG ASRRAT 2023 - Glorya Oktavianti; Ida Bagus Ketut Bayangkara (Universitas Prof.Hazairin,SH Bengkulu, 2024)
Social Return on Investment (SROI) is based on seven principles, namely involving stakeholders, understanding change, being transparent, not claiming too much, providing important input, assessing priorities, and verifying results. The purpose of this study is to determine how social activities affect the calculation of Social Return on Investment (SROI). Social return on investment is a measurement method used to assess the social and environmental impacts of a program. The research was conducted using a qualitative approach by adopting a case study. The purpose of this study is to determine the social impact using the calculation of SROI. Based on SROI research at the PT PLN Nusantara Power company, there are findings obtained from SROI analysis starting from reporting, management, and benefits from social activities related to the object of research to measure the social impact that the company has carried out. Based on the results of SROI research on social program, it can be concluded that every RP 1 invested in PT PLN Nusantara Power's social program will generate social reciprocity of Rp 1.61. This ratio figure has provided economic, social, and environmental benefits.